Everything is skimped now: Food in war times through the eyes of women - Correia, Marta (Cadernos de Literatura Comparada, 2017)
The aim of this paper is not to present critical dystopias as traditionally understood, views of a post-apocalyptic future world where there is a glimmer of hope and a possibility of change amidst a seemingly irreversible chaos. Rather, I intend to consider representations of reality itself as dystopia through diaries, memoirs, reports or works of “faction” written by women enduring or revisiting war times. Through the reading of these multiple texts, I hope to find common ground and identify the role food plays in the lives of people trying to cope with the inevitable scarcity of resources an armed conflict brings. I also attempt to determine whether there is a cultural ideal behind the everyday action that is the sharing of food and, thus, find in Utopian Foodways a tool of resistance which counteracts the fragmentation of society, but also a means to denounce and expose the hypocrisy of those who wage war.